Consumer Satisfaction Analysis on Central Java Best Natural Tourist Destination Based on Trip Advisor Website - Dipa Teruna Awaloedin; Rizki Nurul Nugraha (Westscience Press, 2024)
Consumer satisfaction provides an idea of how well their experience met expectations or exceeded expectations before interacting with the product or service received. A high level of satisfaction will create customer loyalty, positive reviews, and word-of-mouth recommendations, whereas dissatisfaction can create complaints, negative reviews, and reduced customers. The purpose of this study is to understand the level of consumer satisfaction with the best natural tourist destination in Central Java based on reviews and ratings on the TripAdvisor website. This type of research is qualitative, with qualitative descriptive analysis methods, whose data collection is carried out by observing consumer reviews on the top 5 natural tourist destination from the list of the best natural tourist destination in Central Java based on the TripAdvisor website. The results showed that consumer satisfaction with the five best natural tourist destination in Central Java based on the TripAdvisor website, each destination must provide accessibility and facilities with good quality. Natural tourist destination require good accessibility, such as road access that can be easily used by visitors and access to complete information for visitors to be safer in exploring destinations. Adequate facilities with good quality.